P010 Characterization of distinct dendritic cell subsets in the context of chronic inflammation. (March 2019) - Coutant, F; Zhang, J; Miossec, P
Abstract : Career situation of first and presenting author: Assistant. Introduction: Dendritic cells (DCs) are central regulators of the balance between immunity and tolerance, and alteration of the specialized DCs system is a common feature in chronic inflammatory diseases, such as rheumatoid arthritis (RA). In RA, synovial tissues are characterized by aberrant distribution of DCs populations, with altered phenotype. However, an in-depth characterization of the altered phenotype and functions of DCs in RA has been hampered by a lack of specific DCs markers and relevant in vitro culture model. Objectives: To perform an in-depth phenotypic characterization of DCs found in RA joints with an extensive panel of monoclonal antibodies specific of DCs, and to establish a relevant in vitro culture model to generate DCs resembling to those found in joints. Methods: Flow cytometry was used for analysis of cell surface molecules expressed on DCs found in RA synovial fluid (SF). Staining was performed with a panel of 100 mouse monoclonal antibodies specific of DCs, generated by immunization with different subsets of human DCs. Phenotype of DCs from synovial fluid was then compared to the phenotype of monocytes co-cultured in vitro with synoviocytes from RA patients, in presence or not of synovial fluid, or cytokines. Results: In RA SF patients, two main DCs subsets were identified, with distinct surface protein phenotypes. One subset was characterized by markers of plasmacytoid DCs (CD303, CD123), whereas the other subset expressed markers of myeloid/conventional DCs (CD11c, DCIR). This last subset of DCs expressed some markers found on inflammatory DCs, the main inducers of Th17 cells in RA joints. Surprisingly, the two subsets of DCs expressed also surface proteins shared by synoviocytes. Culture of human monocytes with synoviocytes and/or combination of pro-inflammatory cytokines (TNF, M-CSF, IL-4) yielded DCs with a phenotype close to the phenotype of conventional DCs found in RA synovial fluid. Conclusions: We uncovered previously unreported phenotypic heterogeneity of DCs in a chronic inflammatory context, and characterized two main subsets of DCs. The next steps will be to understand the consequences of this heterogeneity on the pathogenicity of the disease. This will be facilitated by our relevant in vitro culture model that allows the generation of DCs, closely resembling those found in joints of patients with RA. Disclosure of Interest: None declared.